1998
DOI: 10.1255/ejms.238
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid peroxidation products are metabolized by hydrogenation in porcine liver tissue

Abstract: Homogenization of mammalian tissue activates enzymes which cause degradation. This effect was used to elucidate the metabolism of 13-S-hydroxy-9,11-octadecadienoic acid (13-S-HODE) and 9-S-hydroxy-10,12-octadecadienoic acid (9-S-HODE), physiologically active products of lipid peroxidation (LPO) processes, by electron ionization GC/MS. 13-S-HODE was added to a porcine liver homogenate, samples withdrawn at timed intervals and extracts of polar fatty acids then subjected to GC/MS analysis, after methylation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A minor contribution to this ion may result from secondary cleavage of the m/z 259 ion by loss of CH 3 OH. Location of the double bond between C-12 and C-13 was confirmed based on the presence of the fragment ion at m/z 124 corresponding to 1,3-nonadiene, as described previously [23]. a Trimethylsilyl-ether of isoricinoleic acid FAME, b 9oxo-cis-12-octadecenoic acid FAME, c Dimethyl disulfide adduct of 9-oxo-cis-12octadecenoic acid FAME.…”
Section: Identification Of Fasmentioning
confidence: 95%
“…A minor contribution to this ion may result from secondary cleavage of the m/z 259 ion by loss of CH 3 OH. Location of the double bond between C-12 and C-13 was confirmed based on the presence of the fragment ion at m/z 124 corresponding to 1,3-nonadiene, as described previously [23]. a Trimethylsilyl-ether of isoricinoleic acid FAME, b 9oxo-cis-12-octadecenoic acid FAME, c Dimethyl disulfide adduct of 9-oxo-cis-12octadecenoic acid FAME.…”
Section: Identification Of Fasmentioning
confidence: 95%
“…The position of the double bond between C12 and C13 has previously been confirmed for IR from N. oleander by oxidative cleavage [8]. It has also been suggested that the ion at m/z 124 seen in the mass spectrum of TMS-IR-FAMES corresponds to ionized 1,3 nonadiene, a fragment from the methyl end of IR resulting from cleavage αto the OTMS group, placing the double bond between carbons 12 and 13 [22]. The acyl composition of seeds of W. natalensis and S. speciosus (syn.…”
Section: Seed Acyl Compositionmentioning
confidence: 67%
“…Nevertheless they suffer slow degradation. They are mainly degraded primarily by hydrogenation and not by oxidation, as might be assumed 32. The ability to remove LOH by reduction decreases with increasing age.…”
Section: Markers For Lipid Peroxidation Processesmentioning
confidence: 91%